Determination of Diagnostic Dilemma at Preoperative Biopsy Diagnosis of Oral Cavity Lesions with Recommendations - Chaturvedi, Madhu I.; Pathan, Arshad K. (New Frontiers in Medicine and Medical Research Vol. 14, 2021)
Background: Oral cavity lesions of varied nature present in varying patterns from a plaque to a proliferative growth. Biopsy is an important preoperative diagnostic tool for the diagnosis of lesions ranging from simple tumour like lesions to malignancies and deciding the treatment and extent of surgery. At times it becomes difficult for a pathologist, to decide exact nature of the growth at biopsy. The present study was conducted to evaluate the role of biopsy in the assessment of true nature of oral cavity lesions and its problems and pitfalls. The authors share their experience and dilemma during reporting and views to solve them. Methods: All the punch biopsies and subsequent surgical resections of oral cavity received in department of pathology were reviewed over a period of two years. They were subjected to routine tissue processing in automatic tissue processor, 4-5 microns section cutting and routine H& E staining. Histopathology was evaluated. All the tumours were classified according to WHO classification of Head and Neck tumours. Tumour like lesions was evaluated on the basis of features described by various authors in the literature. Specificity, sensitivity, accuracy, percentage of false negative and false positive, and positive and negative predictive value of the oral cavity biopsy was evaluated. Result: Majority of the oral cavity lesions irrespective of nature, presented as exophytic proliferative growth (83.9%). The diagnostic accuracy of biopsy for evaluating oral cavity lesions was 95.1%. There were 6.9% false negative reports. Sensitivity and positive predictive value of the method to detect malignant and premalignant lesions was 93.1% and 100% respectively, whereas, specificity and negative predictive value was 100% and 85%. In total 19 cases, problem of histopathology assessment was encountered. Conclusion: To prevent problems and pitfalls in assessing the nature of oral cavity lesion prior to surgery, the reporting pathologist should take utmost care in proper orientation and processing of the tiny oral cavity biopsies, be aware of accurate definitions, characteristic features and criteria of malignancy and should have a close co-ordination with the treating surgeon.